Aggregation and the Demand for New and Used Automobiles - Johnson, Terry R. (Review of Economic Studies, 1978)
Journal Article Aggregation and the Demand for New and Used Automobiles Get access Terry R. Johnson Terry R. Johnson Stanford Research Institute Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 45, Issue 2, June 1978, Pages 311–327, https://doi.org/10.2307/2297346 Published: 01 June 1978 Article history Received: 01 August 1976 Accepted: 01 February 1977 Published: 01 June 1978